China Opposing Nuclear Nonproliferation: A Rational Policy with an Ideological Mask. (March 2021) - Zhang, Hongyu
Why did a would-be recognized nuclear state oppose nonproliferation for two decades, but then change its position in 1984? Based on extensive fieldwork in Beijing where the author conducted 20 interviews with high-profile Chinese government and military officials, ambassadors of disarmament, and nuclear and astronautic scientists, this article argues that China openly opposed nonproliferation to give its nascent nuclear program time to achieve a retaliatory capability. Once this goal was fulfilled in the mid-1980s, China began accepting nonproliferation norms. While China's fervent opposition seemed ideological in a revolutionary era, it was indeed a rational behavior in pursuit of security interests.